The "Gulliver Effect" and the "Optimal Divergence" Approach to Trade Policies : The Case of Nepal. (IMF Working Papers; Working Paper, 1988)
The relevant 'size' of an economy is affected by its environment. A country could be small in the world economy yet become big in relation to its smaller neighbors, imposing on them its relative price structure and the consequences of its trade policies. We examine here the consequences of such a 'Gulliver' effect, looking at the case of Nepal whose economy is closely linked to the economy of India. Since India's protective policies are not optimal for Nepal, we consider the various alternatives for Nepal. The 'optimal divergence' is for Nepal to allow the free import of intermediate and capital goods, while, for import-competing industries, it cannot depart from India's trade policy.